2012
DOI: 10.1002/bjs.7772
|View full text |Cite
|
Sign up to set email alerts
|

Use of Hospital Episode Statistics to investigate abdominal aortic aneurysm surgery

Abstract: Coding consistency was high. The proposed framework could define homogeneous groups by combining diagnosis, procedure and administrative codes. It also allows an assessment of potential miscoding at national and hospital level.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 20 publications
2
19
0
Order By: Relevance
“…Results from the first of these audits suggest that 10.5% of primary procedures are coded incorrectly although there was wide variation between different trusts and the inaccuracies did not necessarily mean that patients were categorised incorrectly 20 . Another study looking at aortic aneurysm surgery found that coding accuracy appeared to be high if diagnostic, operative and administrative codes were compared, and accuracy could be improved further if they were combined, 21 similar to our study.…”
Section: Discussionsupporting
confidence: 87%
“…Results from the first of these audits suggest that 10.5% of primary procedures are coded incorrectly although there was wide variation between different trusts and the inaccuracies did not necessarily mean that patients were categorised incorrectly 20 . Another study looking at aortic aneurysm surgery found that coding accuracy appeared to be high if diagnostic, operative and administrative codes were compared, and accuracy could be improved further if they were combined, 21 similar to our study.…”
Section: Discussionsupporting
confidence: 87%
“…10 The richness of the data also makes it possible to develop coding frameworks and data quality criteria to identify hospitals with divergent coding practices by combining diagnosis, procedure, and administrative codes. 16 A number of recent publications have demonstrated that when analysed carefully, HES is a valuable source of data to explore patterns of care as well as supporting epidemiological studies related to childbirth. [17][18][19] This study included half of all vaginal singleton term births in primiparous women who delivered in an NHS hospital over a 12-year period.…”
Section: Discussionmentioning
confidence: 99%
“…15 Administrative databases also lack the detail of clinical information systems or case notes, and it was not possible to control for risk factors that could not be recorded using ICD-10 codes, such as size of uterine cavity.…”
Section: Strengths and Limitationsmentioning
confidence: 99%